Energy-saving 3D VC uniform temperature plate with flexible full-laminated capillary support structure
Patent Information
- Application Number
- CN202611380723.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-07
- Publication Date
- 2026-10-20
AI Technical Summary
1.通过铜毛细层与柔性支撑肋共同构成铜毛细支撑结构,能够在三维相变腔体内提供液体回流路径、蒸汽通道间隔和薄型壳体支撑,使均温板在较小厚度下兼顾相变传热和腔体间隔保持。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of electronic heat dissipation and temperature equalization technology, specifically to an energy-saving 3DVC temperature equalization plate with a flexible, fully bonded capillary support structure. Background Technology
[0002] As high-performance mobile terminals, AI edge devices, server modules, automotive electronics, and highly integrated packaged chips continue to evolve towards thinner profiles, higher power densities, and longer-term stable operation, the local heat flux density generated by heat-generating components within limited installation space is constantly increasing. As a key heat dissipation component connecting the heat source and the heat dissipation structure, vapor chambers need to simultaneously possess rapid phase-change heat transfer, in-plane temperature uniformity, low contact thermal resistance, pressure resistance, and assembly adaptability within millimeter or even sub-millimeter thicknesses. Especially in portable electronic devices, heat dissipation components must not only reduce hotspot temperature rise but also adapt to thinner housings, differences in heat source contours, assembly pressure fluctuations, and interface changes caused by repeated thermal cycling. Therefore, developing thin vapor chambers that combine cavity structural integrity, capillary recirculation capability, full interface bonding capability, and liquid thermally conductive medium confinement capability is of great significance for improving the thermal management efficiency of electronic devices, extending device lifespan, and improving energy consumption control.
[0003] Existing ultrathin vapor chambers typically maintain cavity spacing and achieve liquid reflux using copper powder sintered capillary layers, copper mesh capillary layers, support pillars, or internal support frames. For example, US6880626B2 discloses a vapor chamber scheme with grooved capillary structures and support structures, CN105352352A discloses an ultrathin vapor chamber device with support pillars and porous metal capillary cores, and CN115930645B discloses an ultrathin flexible vapor chamber structure and its preparation method. However, these schemes mainly focus on capillary reflux and support within the cavity, with insufficient attention paid to full adhesion of the external interface on the heating element side, liquid metal confinement, and interface compatibility control. On the other hand, existing liquid metal thermal interface schemes utilize liquid metal to reduce contact thermal resistance, but liquid metal diffusion, flow, overflow, and long-term stability on the copper surface require additional interface layers and confinement structures. Therefore, existing technologies still face the challenge of simultaneously addressing the issues of phase change cavity support and heat transfer resistance, and the difficulty in simultaneously ensuring the thermal conductivity and confinement reliability of exposed liquid metal. Summary of the Invention
[0004] The purpose of this invention is to provide an energy-saving 3DVC vapor chamber with a flexible, fully bonded capillary support structure, so as to improve the problem of balancing cavity support, working fluid reflux, interface heat conduction and liquid alloy confinement in thin vapor chambers.
[0005] To achieve the above objectives, the present invention provides the following technical solution: This invention provides an energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure, comprising a closed shell, a copper capillary support structure, deionized water, a flexible, fully-fitted surface, a nickel interface layer, a liquid alloy heat conduction unit, and a polytetrafluoroethylene limiting frame.
[0006] The enclosed shell includes a first copper sheet and a second copper sheet, which are sealed together at the periphery, forming a three-dimensional phase change cavity within the enclosed shell. A copper capillary support structure is disposed within the three-dimensional phase change cavity, including a copper capillary layer and multiple flexible support ribs. The flexible support ribs extend from the copper capillary layer towards another copper sheet and abut against it, forming a vapor channel between the evaporation zone and the condensation zone.
[0007] The flexible fully bonded surface is located on the side of the first copper sheet facing away from the three-dimensional phase change cavity. The flexible fully bonded surface includes a microgroove confinement region corresponding to the heating element of the electronic device. A nickel interface layer covers at least a portion of the bottom and walls of the microgroove confinement region; a gallium indium tin liquid alloy heat conduction unit is at least partially confined and filled within the microgroove confinement region and contacts the nickel interface layer; a polytetrafluoroethylene (PTFE) limiting frame is disposed around the periphery of the microgroove confinement region. The liquid alloy heat conduction unit forms an exposed thermal interface on one side of the flexible fully bonded surface.
[0008] In this invention, the flexible fully-fitted surface refers to the interface heat-conducting region jointly formed by the microgroove confinement area on the outer side of the first copper sheet, the nickel interface layer, the gallium indium tin liquid alloy heat conduction unit, and the polytetrafluoroethylene limiting frame; wherein, "flexible" refers to the ability of the exposed heat-conducting interface of the liquid alloy to conform to the micro-contour of the surface of the heating element under an installation pressure of 0.020-0.200MPa, and "fully-fitted" means that the microgroove confinement area corresponding to the projection area of the heating element forms a continuous confined heat-conducting interface, which does not mean that the first copper sheet or the flexible support rib undergoes macroscopic bending, nor is it limited to 100% geometric contact rate.
[0009] In this invention, the flexible support rib refers to a support rib formed of porous sintered copper material, which can adapt to the height tolerance of the cavity during the sealing and pressing of the first copper sheet and the second copper sheet, and is used to maintain the three-dimensional phase change cavity spacing after sealing; the flexible support rib is not limited to undergoing large bending during use.
[0010] Furthermore, both the first and second copper sheets use copper as the main heat conductor, the copper capillary layer and the flexible support ribs are both formed of copper, the nickel interface layer is formed of nickel, the liquid alloy heat conduction unit is a gallium indium tin liquid alloy heat conduction unit, the gallium indium tin liquid alloy heat conduction unit includes gallium, indium and tin, and the polytetrafluoroethylene limiting frame is formed of polytetrafluoroethylene.
[0011] The maximum total thickness of the energy-saving 3DVC heat spreader is 0.25-1.20 mm, the microgroove depth of the microgroove confinement area is 10-120 μm, the microgroove width is 20-300 μm, the spacing between the center lines of adjacent microgrooves is 50-800 μm, and the microgroove depth is less than the single-piece thickness of the first copper sheet.
[0012] Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, the content of gallium is 68.0-69.5 wt%, the content of indium is 20.5-22.5 wt%, and the content of tin is 9.0-11.0 wt%, with the combined content of gallium, indium, and tin satisfying a total content of 99.0-100.0 wt%. The residual components other than gallium, indium, and tin are unavoidable metal impurities and oxides, and the oxygen content is determined separately based on the total sample mass of the liquid alloy heat conduction unit.
[0013] The gallium indium tin liquid alloy heat conduction unit occupies 30-90% of the total volume of the microgroove confinement area, and has an equivalent exposed thickness of 3-50 μm on one side of the flexible fully bonded surface.
[0014] The term "adjacent microslot spacing" as used in this paper refers to the distance between the center lines of adjacent microslot openings. The "slot filling rate" is the ratio of the volume of gallium indium tin liquid alloy inside the microslot to the total volume of the microslot. The "equivalent exposed thickness" is the ratio of the volume of gallium indium tin liquid alloy outside the microslot opening plane to the total area of the microslot confinement area opening. The "area coverage rate" is the ratio of the coverage area of gallium indium tin liquid alloy on the microslot confinement area opening plane to the total area of the microslot confinement area opening.
[0015] The height of the three-dimensional phase change cavity is the vertical distance between the inner surfaces of the first and second copper sheets. The total thickness of the enclosed shell is the maximum vertical distance between the outer surfaces of the first and second copper sheets; the maximum total thickness of the energy-saving 3DVC heat spreader is the maximum vertical distance from the outer surface of the second copper sheet facing away from the three-dimensional phase change cavity to the upper surface of the polytetrafluoroethylene limiting frame.
[0016] Let the thickness of the PTFE limiting frame before press-fitting be tPTFE, the actual depth of embedding in the annular limiting groove be dE, the equivalent exposed thickness of the liquid alloy be tL, and the height of the upper surface of the PTFE limiting frame above the exposed surface of the liquid alloy be hF. Then, hF = tPTFE - dE - tL, and dE is not greater than the depth of the annular limiting groove. The projection of the heating element of the electronic device in contact with the flexible fully bonded surface is located within the inner opening of the PTFE limiting frame, so that the contact area of the heating element does not form a thermally conductive contact path with the upper surface of the PTFE limiting frame.
[0017] Furthermore, the gallium indium tin liquid alloy thermal conductivity unit is prepared through the following steps: A1. Weigh 68.0-69.5 wt% of metallic gallium, 20.5-22.5 wt% of metallic indium and 9.0-11.0 wt% of metallic tin based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit to be prepared; A2. Place metallic gallium, metallic indium, and metallic tin in a molten container, and heat at 235-240℃ under a nitrogen or argon atmosphere while stirring for 0.5-3.0 h to form a homogeneous metallic molten phase; A3. After stopping stirring, let stand for 5-30 minutes, and remove the oxide film on the surface of the homogeneous molten metal phase using a ceramic scraper under nitrogen or argon atmosphere protection. A4. Cool the homogeneous molten metal phase after removing the oxide film to 20-30℃ to obtain a gallium indium tin liquid alloy thermal conductivity unit; A5. The total content of gallium, indium and tin in the gallium-indium-tin liquid alloy heat conduction unit is 99.0-100.0 wt%, the oxygen content is 10-1000 ppm, and it remains liquid at 20-30℃ without solid phase precipitation.
[0018] The oxygen content of the liquid alloy thermal conduction unit was determined by inert gas melting infrared absorption method, with three samples tested in parallel for each batch. The tested liquid alloy samples were left to stand at 20-30℃ for 24 hours, and the absence of visible solid phase precipitation was confirmed by optical microscopy and differential scanning calorimetry.
[0019] Furthermore, the microgroove confinement region and the nickel metal interface layer are formed through the following steps: B1. Provide the first copper sheet; B2. A microgroove confinement region is formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity by precision stamping, laser processing or chemical etching. The microgroove depth is 10-120μm, the microgroove width is 20-300μm, the spacing between the center lines of adjacent microgrooves is 50-800μm, and the microgroove depth is less than the thickness of a single piece of the first copper sheet. B3. Physical vapor deposition was performed on the microgroove confinement area using metallic nickel as the deposition source; B4. A metallic nickel interface layer with a thickness of 0.2-5.0 μm is formed on at least a portion of the surface of the bottom and wall of the microgroove confinement region; B5. The size variation coefficient of the microgroove confinement region is 1-15%, and the nickel metal interface layer continuously covers 80-100% of the bottom area of the microgroove confinement region.
[0020] The first copper sheet, after completing the microgroove confinement region processing, is placed in a physical vapor deposition (PVD) apparatus. Nickel is used as the deposition source, and argon is used as the deposition atmosphere. PVD is performed at 20-120℃, 0.0000001-0.000001MPa, and for 5-60 minutes. The PVD is conducted using DC magnetron sputtering. The nickel target purity is not less than 99.9%, and the target-substrate distance is 80-150 mm. During deposition, the first copper sheet rotates at 5-30 rpm, and deposition is performed sequentially in the normal direction and at incident directions ±30° relative to the normal.
[0021] Furthermore, the copper capillary support structure is formed through the following steps: C1. Copper is selected as the capillary material, which is one or more of copper powder, copper mesh or copper fiber, wherein the copper powder has a particle size of 5-80μm, the copper mesh has a pore size of 20-200μm, and the copper fiber has a diameter of 5-50μm. C2. The capillary material is laid on the side of the first or second copper sheet facing the three-dimensional phase change cavity to form a copper capillary layer with a thickness of 20-250μm; C3. Multiple flexible support ribs with a height of 40-300μm, a width of 30-500μm, and a spacing of 0.20-2.00mm are formed on the copper capillary layer; C4. Sintering of capillary materials and flexible support ribs; C5. After sintering, the copper capillary support structure is obtained by cooling. C6. The porosity of the copper capillary support structure is 35-75 vol, and the ratio of the bonding area between the copper capillary layer and the first or second copper sheet is 70-100%.
[0022] In forming the flexible support ribs, a metal mask with a patterned opening for the flexible support ribs is placed over the surface of the copper capillary layer. Copper powder is then locally deposited within the patterned openings to form a rib-shaped preform. After removing the metal mask, the copper capillary layer and the rib-shaped preform are sintered together to form multiple flexible support ribs. The sum of the thickness of the copper capillary layer and the height of the flexible support ribs is matched to the height of the three-dimensional phase change cavity, allowing the flexible support ribs to abut against another copper sheet after sealing.
[0023] The copper capillary layer and flexible support ribs are sintered at 600-900℃ for 10-60 min in a nitrogen or argon atmosphere, and then cooled to 20-60℃ in a nitrogen or argon atmosphere to obtain a copper capillary support structure with a porosity of 35-75 vol% and a copper capillary layer bonding area with the copper sheet it is located in that ratio of 70-100%.
[0024] The porosity ε of the copper capillary support structure is calculated as ε = [1 - m / (ρCu × V)] × 100%, where m is the mass of the copper capillary support structure after removing the copper sheet, ρCu is the density of copper, and V is the outer volume of the copper capillary support structure. The bonding area ratio is the ratio of the actual sintered bonding area between the copper capillary layer and the copper sheet to their projected contact area, and is statistically analyzed using microscopic images from no less than 10 cross-sectional fields of view.
[0025] Furthermore, the polytetrafluoroethylene (PTFE) limiting frame is formed through the following steps: D1. Provide polytetrafluoroethylene film; D2. Cut the polytetrafluoroethylene film into a frame-shaped structure; D3. An annular limiting groove is formed around the periphery of the microgroove confinement area; D4. Embed the frame structure into the annular limiting groove and press it in to obtain the polytetrafluoroethylene limiting frame; D5. The upper surface of the PTFE limiting frame is 5-50 μm higher than the surface of the liquid alloy heat conduction unit exposed on the flexible full-fit side, and the PTFE limiting frame is not connected to the three-dimensional phase change cavity.
[0026] Furthermore, the microgroove confinement area includes a central heat-conducting groove group and a peripheral backflow blocking groove group. The central heat-conducting groove group is located within the projection area of the heating element of the electronic device, and the peripheral backflow blocking groove group is arranged around the central heat-conducting groove group. The groove density of the central heat-conducting groove group is 5-30 grooves / cm, and the groove density of the peripheral backflow blocking groove group is 10-60 grooves / cm.
[0027] The groove density is the number of microgroove centerlines perpendicular to the microgroove extension direction per unit length; when the distance between adjacent microgroove centerlines is pμm, the groove density is 10000 / pgroove / cm. The microgroove width, microgroove depth, and distance between adjacent microgroove centerlines of the central heat-conducting groove group and the peripheral return flow blocking groove group can be set differently, and all fall within the corresponding range of the microgroove width, microgroove depth, and distance between adjacent microgroove centerlines.
[0028] Furthermore, the three-dimensional phase change cavity includes an evaporation zone, a condensation zone, and a vapor channel connecting the evaporation zone and the condensation zone. The evaporation zone and the micro-groove confinement zone correspond to each other in the thickness direction. The filling rate of deionized water in the three-dimensional phase change cavity is 10-40 vol.
[0029] The resistivity of the deionized water is not less than 15 MΩ·cm. Before injection, the deionized water is degassed under vacuum at 50-80℃ and 0.005-0.020 MPa for 10-30 min, and then cooled to 20-30℃ under nitrogen protection. The filling rate is the ratio of the injected deionized water volume to the effective volume of the three-dimensional phase change cavity; the effective volume of the three-dimensional phase change cavity is the volume of the three-dimensional phase change cavity after deducting the volume of the copper capillary support structure from the geometric volume of the three-dimensional phase change cavity.
[0030] Furthermore, the area coverage of the liquid alloy heat conduction unit within the microgroove confinement area is 60-98%, and the mass of the free liquid alloy located within the PTFE confinement frame and outside the microgroove confinement area accounts for 0-5 wt% of the total mass of the liquid alloy heat conduction unit.
[0031] Furthermore, the thickness of the first and second copper sheets is 0.08-0.30 mm, the height of the three-dimensional phase change cavity is 40-500 μm, and the flexible full-fit surface forms thermal contact with the heating element of the electronic device under an installation pressure of 0.020-0.200 MPa.
[0032] This invention employs a design that couples a copper capillary support structure within a three-dimensional phase-change cavity with a flexible, fully-fitted external liquid alloy confinement structure. This design achieves a balance between the integrity of the thin-walled cavity structure, phase-change heat transfer efficiency, interfacial thermal conductivity, and liquid alloy confinement. The copper capillary layer and flexible support ribs form an internal network that serves both as capillary recirculation and cavity spacing. The microgroove confinement region, the nickel interface layer, the gallium indium tin liquid alloy thermal conduction unit, and the PTFE confinement frame form a restricted exposed thermally conductive interface.
[0033] This invention also discloses a method for preparing an energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure, comprising the following steps: S1. Provide a first copper sheet and a second copper sheet, both of which use copper as the main heat conductor; S2. A microgroove confinement region is formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity to be formed, and a nickel interface layer made of metallic nickel is formed on at least part of the bottom and wall of the microgroove confinement region. S3. A copper capillary support structure made of copper is formed on the side of the first copper sheet or the second copper sheet facing the three-dimensional phase change cavity to be formed; S4. The first copper sheet and the second copper sheet are joined and sealed to form a shell with a three-dimensional phase change cavity and a vacuum injection port connected to the three-dimensional phase change cavity; S5. After evacuating the three-dimensional phase change cavity through the vacuum injection port, deionized water that has undergone degassing treatment is injected and the cavity is sealed. S6. Fill the microgroove confinement area with the pre-prepared liquid alloy heat conduction unit, and use scraping and rolling to shape it to obtain the predetermined groove filling rate, equivalent exposed thickness and area coverage. S7. A polytetrafluoroethylene (PTFE) limiting frame is set around the periphery of the micro-groove confinement area to obtain an energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure.
[0034] Furthermore, in step S2, the microgroove confinement area is formed by one of laser processing, precision stamping or chemical etching. The depth of the formed microgroove is 10-120μm, the width of the microgroove is 20-300μm, the spacing between the center lines of adjacent microgrooves is 50-800μm, and the depth of the microgroove is less than the thickness of a single piece of the first copper sheet.
[0035] Furthermore, in step S3, the copper capillary support structure is formed by copper powder sintering, copper mesh pressing and sintering, or copper fiber sintering.
[0036] Furthermore, in step S4, the sealing method is one of laser welding, diffusion welding or brazing, and the height of the three-dimensional phase change cavity formed after sealing is 40-500μm.
[0037] Furthermore, in step S5, the absolute pressure of the three-dimensional phase change cavity after vacuuming is 0.0000001-0.0005 MPa. Before injection, the deionized water is degassed under vacuum at 50-80℃ and 0.005-0.020 MPa for 10-30 minutes. The filling rate of the deionized water is 10-40 vol%. After sealing, the total thickness of the sealed shell is 0.25-1.20 mm.
[0038] Further, in step S6, the gallium indium tin (CITi) liquid alloy heat conduction unit is filled into the microgroove confinement area at 20-80℃ and a filling pressure of 0.01-0.30 MPa. After removing excess free liquid alloy located outside the microgroove confinement area by scraping, the microgroove confinement area is rolled and shaped 1-5 times with a rolling pressure of 0.020-0.200 MPa. The filling rate of the groove after shaping is 30-90 vol%, the equivalent exposed thickness is 3-50 μm, the area coverage is 60-98%, and the mass of free liquid alloy located within the PTFE confinement frame and outside the microgroove confinement area accounts for 0-5 wt% of the total mass of the CITi liquid alloy heat conduction unit.
[0039] Furthermore, the PTFE film has a thickness of 20-150 μm, and is cut to form a frame structure with a width of 0.10-1.50 mm. An annular limiting groove with a depth of 5-80 μm is formed around the periphery of the microgroove confinement area. After the frame structure is embedded into the annular limiting groove, it is press-fitted for 10-120 s at 20-120℃ and 0.05-0.50 MPa to obtain a PTFE limiting frame surrounding the microgroove confinement area. The upper surface of the PTFE limiting frame protrudes 5-50 μm above the exposed surface of the gallium indium tin liquid alloy heat conduction unit, and the PTFE limiting frame is not connected to the three-dimensional phase change cavity.
[0040] This invention employs a preparation method that involves first constructing a microgroove confinement region and a nickel metal interface layer, then forming a copper capillary support structure, sealing and vacuuming the liquid injection, filling a gallium indium tin liquid alloy heat conduction unit, and setting a polytetrafluoroethylene (PTFE) limiting frame. This allows the three-dimensional phase change cavity, copper capillary support structure, nickel metal interface layer, and microgroove liquid alloy unit to respectively perform capillary reflux, cavity support, interface contact, and exposed heat conduction functions in space.
[0041] Beneficial technical effects 1. The copper capillary support structure is formed by the copper capillary layer and the flexible support ribs. It can provide a liquid reflux path, vapor channel spacing and thin shell support in the three-dimensional phase change cavity, so that the heat spreader can take into account both phase change heat transfer and cavity spacing with a small thickness.
[0042] 2. By setting a microgroove confinement area on the flexible fully bonded surface and setting a metallic nickel interface layer on at least part of the bottom and wall of the groove, the gallium indium tin liquid alloy heat conduction unit can form an exposed heat conduction interface in the confined space, which helps to reduce the micro-gaps between the heating element and the heat spreader and restricts the lateral migration of the liquid alloy under assembly pressure.
[0043] 3. A polytetrafluoroethylene (PTFE) limiting frame is set around the periphery of the microgroove confinement area, and its upper surface is higher than the exposed surface of the gallium indium tin liquid alloy heat conduction unit. This can form physical limits and edge barriers during installation and pressing to define the distribution boundary of the liquid alloy.
[0044] 4. By combining the central heat conduction groove group with the peripheral backflow blocking groove group, the liquid alloy heat conduction in the projection area of the heating element and the liquid alloy confinement in the peripheral area form a spatial division of labor, which is conducive to improving the utilization rate of the interface heat conduction area.
[0045] 5. By implementing the vacuum injection, copper capillary support structure sintering, nickel interface layer deposition, liquid alloy filling and polytetrafluoroethylene limiting frame press fitting in stages, the process interference between different structural units can be reduced, and the thin shell, phase change cavity and external heat conduction interface can form a composite structure. Attached Figure Description
[0046] Figure 1 The graphs show the liquid alloy retention rates after thermal cycling for Examples 1, 5, and 11.
[0047] Figure 2 The graph shows a comparison of the extreme heat load and in-plane temperature difference for Example 1, Comparative Example 7, and Comparative Example 8.
[0048] Figure 3 The graphs show the interface thermal resistance retention curves before and after thermal cycling for Examples 1, 8, and 11.
[0049] Figure 4This is a graph showing the effect of the tank filling rate on the interfacial thermal resistance and liquid alloy retention rate in Example 1.
[0050] Figure 5 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 5 Figure a in the image is a macroscopic optical photograph of the final product of Example 1; Figure 5 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 11.
[0051] Figure 6 The images show a comparison of the SEM morphology of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 6 Figure a in the figure is a magnified SEM image of the outer thermally conductive region of the final product of Example 1. Figure 6 Figure b in the figure shows the surface SEM morphology of the outer thermally conductive region of the final product in Comparative Example 11. Figure 6 Figure c in the figure is a cross-sectional SEM image of the outer thermally conductive zone of the final product of Example 1; Figure 6 Figure d in the figure is a cross-sectional SEM image of the thermally conductive zone on the outer side of the final product in Comparative Example 11. Detailed Implementation
[0052] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.
[0053] Example 1 This embodiment prepares an energy-saving 3DVC vapor chamber with a flexible, fully-fitted capillary support structure for heat dissipation of localized heating elements in portable electronic devices. The sample dimensions are 60mm × 40mm, with a maximum total thickness of 0.25mm. Both the first and second copper sheets are commercially available high-purity copper sheets with a copper content ≥99.9% and a single sheet thickness of 0.09mm. The height of the three-dimensional phase change cavity is set to 60μm, and the evaporation zone and the microgroove confinement zone correspond in the thickness direction.
[0054] S1: The first and second copper sheets were degreased, rinsed with deionized water, and dried with nitrogen. The cleaning temperature was 25℃, and each rinse lasted 2 minutes. The nitrogen purity was ≥99.99%. A microgroove confinement region was formed on the side of the first copper sheet facing away from the three-dimensional phase transition cavity using laser processing. The microgroove depth was 10μm, the microgroove width was 20μm, and the spacing between the center lines of adjacent microgrooves was 50μm. A continuous copper layer was maintained between the bottom of each microgroove and the side of the first copper sheet facing the three-dimensional phase transition cavity. The depth, width, and spacing of 50 microgrooves were measured, and the coefficient of variation for each was 1%.
[0055] S2: The first copper sheet with completed microgroove fabrication is placed in a physical vapor deposition (PVD) apparatus. Nickel is used as the deposition source, argon is used as the deposition atmosphere (argon purity ≥ 99.99%), the deposition temperature is 20℃, the deposition pressure is 0.0000001MPa, and the deposition time is 5 min. A nickel interface layer is formed on the bottom and walls of the microgroove confinement area. The nickel interface layer has a thickness of 0.2 μm and continuously covers 80% of the bottom area of the microgroove confinement area.
[0056] S3: Commercially available copper powder with a copper content ≥99.5% and a particle size of 5μm was selected as the capillary material. The copper powder was laid on the side of the second copper sheet facing the three-dimensional phase transition cavity, forming a 20μm thick copper capillary layer. Multiple flexible support ribs with a height of 40μm, a width of 30μm, and a spacing of 0.20mm were then locally laid using a metal mask. The copper capillary layer and flexible support ribs were sintered at 700℃ for 20 minutes under a nitrogen atmosphere, and then cooled to 20℃ under a nitrogen atmosphere to obtain the copper capillary support structure. In this embodiment, the porosity of the copper capillary support structure is 35 vol%, and the bonding area ratio between the copper capillary layer and the second copper sheet is 70%.
[0057] S4: The first and second copper sheets are aligned so that the copper capillary support structure is located within the three-dimensional phase change cavity, and the flexible support ribs abut against the inner surface of the first copper sheet, forming interconnected vapor channels between multiple flexible support ribs. The periphery of the shell is sealed using laser welding, with a vacuum injection port provided.
[0058] S5: Deionized water with a resistivity of 18.2 MΩ·cm was degassed under vacuum at 50℃ and 0.005 MPa for 10 min, and then cooled to 20℃ under nitrogen protection. The three-dimensional phase change chamber was evacuated to an absolute pressure of 0.0000001 MPa through the vacuum injection port, and then degassed deionized water was injected with a deionized water filling rate of 10 vol%. The vacuum injection port was then sealed.
[0059] S6: Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, weigh out 68.5 wt% gallium, 21.5 wt% indium, and 10.0 wt% tin. All three metals are commercially available high-purity metals with a purity ≥99.9%. Place the gallium, indium, and tin in a molten container, maintain the temperature at 240°C under a nitrogen atmosphere, and mechanically stir for 0.5 h at a stirring speed of 300 rpm. After stopping stirring, allow the mixture to stand for 5 min, remove the oxide film on the surface of the molten metal phase using a ceramic scraper, and then cool to 20°C to obtain the gallium-indium-tin liquid alloy heat conduction unit. After quality control, the total content of gallium, indium, and tin is 100.0 wt%, the oxygen content is 10 ppm, and it remains liquid with no solid phase precipitation after standing at 20°C for 24 h.
[0060] S7: The gallium indium tin (CITi) liquid alloy heat conduction unit is filled into the microgroove confinement area at 20°C and a filling pressure of 0.01 MPa. Excess free liquid alloy located outside the microgroove confinement area is removed by scraping. Subsequently, the microgroove confinement area is rolled and shaped once with a rolling pressure of 0.020 MPa, so that the filling rate in the groove is 30 vol%, the equivalent exposed thickness is 3 μm, the area coverage is 60%, and the mass of free liquid alloy located within the PTFE confinement frame and outside the microgroove confinement area accounts for 0 wt% of the total mass of the CITi liquid alloy heat conduction unit.
[0061] S8: A commercially available PTFE film with a thickness of 20 μm is provided. The PTFE film is cut into a frame structure with a width of 0.10 mm. An annular limiting groove with a depth of 10 μm is formed around the periphery of the microgroove confinement area. After the frame structure is embedded into the annular limiting groove to an actual depth of 10 μm, it is pressed for 10 s at 20 °C and 0.05 MPa to form a PTFE limiting frame. The PTFE limiting frame surrounds the periphery of the microgroove confinement area, with its upper surface protruding 7 μm above the exposed surface of the gallium indium tin liquid alloy heat conduction unit, and is not connected to the three-dimensional phase change cavity.
[0062] In this embodiment, the thickness of the enclosed shell is 0.24 mm, and the protrusion height of the upper surface of the polytetrafluoroethylene limiting frame relative to the outer surface of the first copper sheet is 10 μm. Therefore, the maximum total thickness of the outer contour is 0.25 mm.
[0063] Quality inspection methods and results: The maximum total outer thickness was measured at 9 locations using a micrometer, with a quality control value of 0.25 mm ± 0.01 mm. Helium mass spectrometry was used to detect leaks in the sealed casing, with a quality control value of 1.8 × 10⁻⁶ mm. - 10 Pa·m 3 / s±0.3×10 -10 Pa·m 3 / s. The interface thermal resistance was tested using a steady-state thermal resistance fixture under an installation pressure of 0.080MPa and a heat input of 40W. The quality control value was 0.185K / W ± 0.008K / W, and the test was repeated 3 times.
[0064] Features and application scenarios of this embodiment: This embodiment employs a smaller microgroove size, a lower liquid alloy filling amount, a thinner nickel interface layer, and a lower deionized water filling rate, making it suitable for heat dissipation scenarios in thin electronic devices where space is limited and the amount of liquid alloy exposure needs to be controlled. The flexible, fully bonded surface forms thermal contact with the heat-generating components of the electronic device under an installation pressure of 0.020 MPa.
[0065] Example 2 This embodiment prepares an energy-saving 3DVC vapor chamber with a flexible, fully bonded capillary support structure for use in high heat flux density chip modules. The sample dimensions are 60mm × 40mm, and the maximum total thickness is 1.20mm. Both the first and second copper sheets are commercially available high-purity copper sheets with a copper content ≥99.9% and a single sheet thickness of 0.30mm. The height of the three-dimensional phase change cavity is 500μm.
[0066] The microgroove confinement region comprises a central heat-conducting groove group and a peripheral recirculation-blocking groove group. The central heat-conducting groove group has a groove depth of 120 μm, a groove width of 300 μm, a spacing of 800 μm between the centerlines of adjacent microgrooves, and a groove density of 12.5 grooves / cm. The peripheral recirculation-blocking groove group has a groove depth of 120 μm, a groove width of 200 μm, a spacing of 500 μm between the centerlines of adjacent microgrooves, and a groove density of 20 grooves / cm. The microgroove depth is less than the thickness of a single piece of the first copper sheet, and the coefficient of variation is 15%.
[0067] The first copper sheet, after the microgroove confinement region processing was completed, was placed in a physical vapor deposition (PVD) apparatus. Nickel was used as the deposition source, argon was used as the deposition atmosphere (argon purity ≥ 99.99%), the deposition temperature was 120℃, the deposition pressure was 0.000001 MPa, and the deposition time was 60 min. A nickel interface layer was formed on the bottom and walls of the microgroove confinement region. The nickel interface layer was 5.0 μm thick and continuously covered 100% of the bottom area of the microgroove confinement region.
[0068] Commercially available copper mesh was selected as the capillary material, with a copper content ≥99.5% and a mesh aperture of 200 μm. The copper mesh was laid on the side of the second copper sheet facing the three-dimensional phase transition cavity, forming a copper capillary layer with a thickness of 200 μm. Copper powder was then locally deposited using a metal mask to form multiple flexible support ribs with a height of 300 μm, a width of 500 μm, and a spacing of 2.00 mm. The copper capillary layer and flexible support ribs were sintered at 900℃ for 60 min under an argon atmosphere and then cooled to 60℃ under an argon atmosphere to obtain the copper capillary support structure. In this embodiment, the porosity of the copper capillary support structure is 75 vol%, and the bonding area ratio between the copper capillary layer and the second copper sheet is 100%.
[0069] The first and second copper sheets are aligned so that the copper capillary support structure is located within the three-dimensional phase change cavity, and the flexible support ribs abut against the inner surface of the first copper sheet. The periphery of the shell is sealed using diffusion welding, leaving the vacuum injection port intact. The three-dimensional phase change cavity is evacuated to an absolute pressure of 0.0005 MPa through the vacuum injection port, and deionized water that has undergone degassing is injected into the cavity at a filling rate of 40 vol%. The vacuum injection port is then sealed.
[0070] Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, 69.0 wt% gallium, 21.5 wt% indium, and 9.5 wt% tin were weighed. The three metals were placed in a molten container and heated at 240°C under an argon atmosphere with mechanical stirring at 600 rpm for 3.0 h. After stirring was stopped, the mixture was allowed to stand for 30 min to remove the oxide film on the surface of the homogeneous molten metal phase, and then cooled to 30°C. The resulting gallium-indium-tin liquid alloy heat conduction unit had a total content of 100.0 wt% gallium, indium, and tin, an oxygen content of 1000 ppm, and remained liquid without solid phase precipitation after standing at 30°C for 24 h.
[0071] Gallium indium tin liquid alloy heat conduction unit was filled into the microgroove confinement area at 80℃ and 0.30MPa filling pressure. After removing excess free liquid alloy by scraping, it was rolled and shaped 5 times with a rolling pressure of 0.200MPa. The filling rate in the groove was 90vol%, the equivalent exposed thickness was 50μm, the area coverage was 98%, and the mass ratio of free liquid alloy located inside the polytetrafluoroethylene confinement frame and outside the microgroove confinement area was 5wt%.
[0072] A commercially available polytetrafluoroethylene (PTFE) film with a thickness of 150 μm is provided. The PTFE film is cut into a frame-shaped structure with a width of 1.50 mm, and an annular limiting groove with a depth of 50 μm is formed around the periphery of the microgroove confinement region. After the frame-shaped structure is embedded into the annular limiting groove to an actual depth of 50 μm, it is press-fitted at 120 °C and 0.50 MPa for 120 s to obtain the PTFE limiting frame. The upper surface of the PTFE limiting frame protrudes 50 μm above the exposed surface of the gallium indium tin liquid alloy heat conduction unit and is not connected to the three-dimensional phase change cavity.
[0073] In this embodiment, the thickness of the enclosed shell is 1.10 mm, and the protrusion height of the upper surface of the polytetrafluoroethylene limiting frame relative to the outer surface of the first copper sheet is 100 μm. Therefore, the maximum total outer thickness is 1.20 mm.
[0074] Quality inspection methods and results: The maximum total thickness of the outer contour was measured using a micrometer, with a quality control value of 1.20 mm ± 0.02 mm; the thickness of the nickel interface layer and the microgroove filling state were measured using cross-sectional microscopic images, with quality control values of 5.0 μm ± 0.2 μm for the nickel interface layer thickness and 90 vol% ± 2 vol% for the groove filling rate; the interface thermal resistance was tested using a steady-state thermal resistance fixture under an installation pressure of 0.080 MPa and a heat input of 40 W, with a quality control value of 0.142 K / W ± 0.006 K / W, and the test was repeated 3 times.
[0075] The features of this embodiment are: a higher liquid alloy filling volume, a thicker nickel interface layer, a higher deionized water filling rate, and a larger installation pressure, making it suitable for high heat flux density chips, power devices, and electronic thermal management scenarios requiring strong interfacial thermal conductivity. The flexible, fully bonded surface forms thermal contact with the heat-generating components of the electronic device under an installation pressure of 0.200 MPa.
[0076] Example 3 In this embodiment, the sample preparation scale is a single 60mm×40mm energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure, and a maximum total outer thickness of 0.70mm. Both the first and second copper sheets are commercially available high-purity copper sheets with a copper content ≥99.9%. The thickness of each copper sheet is 0.20mm, and the height of the three-dimensional phase change cavity is 250μm. The flexible, fully-fitted surface forms thermal contact with the heating element of the electronic device under an installation pressure of 0.080MPa.
[0077] The microgroove confinement region was formed using chemical etching. The central heat-conducting groove group has a microgroove depth of 65 μm, a microgroove width of 160 μm, a spacing of 400 μm between the centerlines of adjacent microgrooves, and a groove density of 25 grooves / cm. The peripheral backflow blocking groove group has a microgroove depth of 65 μm, a microgroove width of 120 μm, a spacing of 250 μm between the centerlines of adjacent microgrooves, and a groove density of 40 grooves / cm. The microgroove size variation coefficient is 8%. The nickel interface layer was formed using physical vapor deposition at a deposition temperature of 70℃, a deposition pressure of 0.0000005 MPa, a deposition time of 30 min, a thickness of 2.5 μm, and a groove bottom coverage area ratio of 92%.
[0078] First, the first and second copper sheets were degreased with ethanol, cleaned with deionized water, and dried with nitrogen. The cleaning temperature was 25°C, and the nitrogen purity was ≥99.99%. Then, a microgroove confinement region was formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity, and a metallic nickel interface layer was deposited under an argon atmosphere.
[0079] Commercially available copper fibers with a copper content ≥99.5% and a diameter of 5μm were used as the copper capillary material. The copper fibers were laid on the side of the second copper sheet facing the three-dimensional phase change cavity to form a 120μm thick copper capillary layer, and multiple flexible support ribs with a height of 130μm, a width of 250μm, and a spacing of 1.00mm were formed. The copper capillary layer and flexible support ribs were sintered at 750℃ for 30 min under a nitrogen atmosphere and then cooled to 40℃ under a nitrogen atmosphere to obtain a copper capillary support structure with a porosity of 55 vol% and a bonding area ratio of 85%.
[0080] After the first and second copper sheets are joined together, the perimeter of the shell is sealed by brazing, leaving the vacuum injection port intact. The three-dimensional phase change chamber is evacuated to an absolute pressure of 0.00002 MPa through the vacuum injection port, and deionized water that has undergone degassing is injected, with a filling rate of 24 vol%. The vacuum injection port is then sealed. The evaporation zone and the micro-groove confinement zone correspond in the thickness direction, and multiple flexible support ribs form a vapor channel connecting the evaporation zone and the condensation zone.
[0081] Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, 68.5 wt% gallium, 20.5 wt% indium, and 11.0 wt% tin were weighed. The three metals were placed in a molten container and heated to 240°C under a nitrogen atmosphere with mechanical stirring at 450 rpm for 1.5 h. After stirring was stopped, the mixture was allowed to stand for 15 min, the oxide film was removed, and then cooled to 25°C. The resulting gallium-indium-tin liquid alloy heat conduction unit had a total content of 100.0 wt% gallium, indium, and tin, an oxygen content of 300 ppm, and remained liquid without solid phase precipitation after standing at 25°C for 24 h.
[0082] Gallium indium tin (GaInT) liquid alloy heat conduction units were filled into the microgroove confinement area at 45°C and a filling pressure of 0.12 MPa. Excess free liquid alloy located outside the microgroove confinement area was removed by scraping, followed by three roll forming processes at a rolling pressure of 0.080 MPa. After forming, the filling rate in the groove was 55 vol%, the equivalent exposed thickness was 20 μm, the area coverage was 80%, and the mass proportion of free liquid alloy located within the PTFE confinement frame and outside the microgroove confinement area was 2 wt%.
[0083] The PTFE (polytetrafluoroethylene) limiting frame is made of commercially available PTFE film with a thickness of 80 μm. The frame structure has a width of 0.80 mm, and the annular limiting groove around the microgroove confinement area has a depth of 30 μm. After embedding the frame structure into the annular limiting groove to an actual depth of 30 μm, it is press-fitted at 60℃ and 0.20 MPa for 60 s, so that the upper surface of the PTFE limiting frame is 30 μm higher than the exposed surface of the gallium indium tin liquid alloy heat conduction unit, while ensuring that the PTFE limiting frame is not connected to the three-dimensional phase change cavity.
[0084] In this embodiment, the thickness of the enclosed shell is 0.65 mm, and the protrusion height of the upper surface of the polytetrafluoroethylene limiting frame relative to the outer surface of the first copper sheet is 50 μm. Therefore, the maximum total outer thickness is 0.70 mm.
[0085] Quality Inspection Methods and Results: Microscopic images were used to statistically analyze the microgroove dimensions. The quality control values were: microgroove depth of the central heat-conducting groove group 65μm±3μm, microgroove width 160μm±7μm, and centerline spacing between adjacent microgrooves 400μm±25μm. Image analysis was used to determine the area coverage, with a quality control value of 80%±2%. A steady-state thermal resistance fixture was used to test the interface thermal resistance under an installation pressure of 0.080MPa and a heat input of 40W. The quality control value was 0.155K / W±0.007K / W, with a test repetition count n=3.
[0086] The applicable scenarios for this embodiment are as follows: This embodiment adopts a copper fiber capillary route and an intermediate process window. The liquid alloy filling amount, the thickness of the nickel interface layer, the microgroove size, and the installation pressure are in the intermediate region, which is suitable for consumer electronics heat dissipation scenarios that need to balance thinness, interface thermal conductivity, and liquid alloy confinement stability.
[0087] Example 4 A 60mm × 40mm sheet-shaped heat spreader was used as the fabrication material, with a maximum total outer thickness of 0.90mm. Both the first and second copper sheets were commercially available high-purity copper sheets with a copper content ≥99.9%, and each sheet had a thickness of 0.24mm. The three-dimensional phase change cavity had a height of 350μm. The flexible, fully bonded surface formed thermal contact with the heating elements of the electronic device under an installation pressure of 0.120MPa.
[0088] A microgroove confinement region was formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity using laser processing. The microgroove depth of the central heat-conducting groove group was 30 μm, the microgroove width was 80 μm, the spacing between the center lines of adjacent microgrooves was 500 μm, and the groove density was 20 grooves / cm. The microgroove depth of the peripheral backflow blocking groove group was 30 μm, the microgroove width was 60 μm, the spacing between the center lines of adjacent microgrooves was 200 μm, and the groove density was 50 grooves / cm. The coefficient of variation for microgroove size was 5%. Using metallic nickel as the deposition source, physical vapor deposition was performed under an argon atmosphere at a deposition temperature of 50℃, a deposition pressure of 0.0000003 MPa, and a deposition time of 20 min, resulting in a 1.2 μm thick metallic nickel interface layer that continuously covered 90% of the bottom area of the microgroove confinement region.
[0089] The copper capillary material employs a composite system of copper powder, copper mesh, and copper fiber, all three being commercially available high-purity copper materials with a copper content ≥99.5%. The copper powder has a particle size of 80 μm, the copper mesh has a pore size of 20 μm, and the copper fiber has a diameter of 50 μm. The copper powder, copper mesh, and copper fiber are laid on the side of a second copper sheet facing the three-dimensional phase transition cavity, forming a copper capillary layer with a thickness of 250 μm. Multiple flexible support ribs with a height of 100 μm, a width of 400 μm, and a spacing of 1.50 mm are then formed using a metal mask. The copper capillary layer and flexible support ribs are sintered at 850℃ for 45 min under an argon atmosphere and then cooled to 50℃ under an argon atmosphere, yielding a copper capillary support structure with a porosity of 65 vol% and a bonding area ratio of 95%.
[0090] The first and second copper sheets are aligned so that the copper capillary support structure is located within the three-dimensional phase change cavity, with the flexible support ribs abutting the inner surface of the first copper sheet. The perimeter is sealed using laser welding, while retaining the vacuum injection port. The three-dimensional phase change cavity is evacuated to an absolute pressure of 0.0001 MPa through the vacuum injection port, and deionized water with a filling rate of 30 vol% is injected. The vacuum injection port is then sealed to form a closed shell. The evaporation zone and the micro-groove confinement zone correspond in the thickness direction, and multiple flexible support ribs form a vapor channel connecting the evaporation and condensation zones.
[0091] Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, 68.5 wt% gallium, 22.5 wt% indium, and 9.0 wt% tin were weighed. All three metals were commercially available high-purity metals with a purity ≥99.9%. The three metals were heated at 240℃ under an argon atmosphere and mechanically stirred at 500 rpm for 2.0 h. After stirring was stopped, the mixture was allowed to stand for 20 min, the oxide film was removed, and then cooled to 28℃ to obtain a gallium-indium-tin liquid alloy heat conduction unit with a total content of 100.0 wt% and an oxygen content of 600 ppm. This liquid alloy remained liquid without solid phase precipitation after standing at 28℃ for 24 h.
[0092] The liquid alloy was filled into the microgroove confinement area at 60℃ and 0.20MPa filling pressure. After being scraped flat, it was rolled and shaped four times with a rolling pressure of 0.150MPa to make the filling rate in the groove 70vol%, the equivalent exposed thickness 35μm, the area coverage 90%, and the mass ratio of the free liquid alloy located inside the polytetrafluoroethylene confinement frame and outside the microgroove confinement area 1wt%.
[0093] A 100μm thick commercially available polytetrafluoroethylene (PTFE) film was cut to form a frame structure with a width of 1.00mm. An annular limiting groove with a depth of 30μm was formed around the periphery of the microgroove confinement area. After embedding the frame structure into the annular limiting groove to an actual depth of 30μm, it was press-fitted at 80℃ and 0.35MPa for 90s to obtain the PTFE limiting frame. The upper surface of the PTFE limiting frame protrudes 35μm above the exposed surface of the gallium indium tin (CITi) liquid alloy heat conduction unit and is not connected to the three-dimensional phase change cavity.
[0094] In this embodiment, the thickness of the enclosed shell is 0.83 mm, and the protrusion height of the upper surface of the polytetrafluoroethylene limiting frame relative to the outer surface of the first copper sheet is 70 μm. Therefore, the maximum total outer thickness is 0.90 mm.
[0095] Quality inspection was conducted using microscopic cross-section analysis, helium mass spectrometry leak detection, and steady-state thermal resistance fixtures. The quality control values were: maximum total outer thickness 0.90 mm ± 0.02 mm and leakage rate 1.5 × 10⁻⁶. -10 Pa·m 3 / s±0.2×10 -10 Pa·m 3 / s, interface thermal resistance 0.160K / W±0.007K / W, test repetition number n=3; the installation pressure of the interface thermal resistance test is 0.080MPa, and the heat input is 40W.
[0096] The process features and application directions of this embodiment: This embodiment adopts composite copper capillary material and microgroove confinement structure, which takes into account capillary reflux, cavity support, liquid alloy confinement and flexible full-fit surface heat conduction, and is suitable for heat dissipation components of electronic devices that require both uniform heat conduction and long-term packaging stability.
[0097] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that no nickel interface layer is formed, and the bottom and wall of the micro-groove confinement area are in direct contact with the gallium indium tin liquid alloy heat conduction unit. Other conditions are the same as in Example 1.
[0098] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that the thickness of the nickel interface layer is 0.1 μm, and the nickel interface layer continuously covers 58% of the bottom area of the microgroove confinement region. Other conditions are the same as in Example 1.
[0099] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that the depth of the microgroove is 5 μm, and the other conditions are the same as those in Example 1.
[0100] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, except that the filling rate in the tank is 20 vol%, and the other conditions are the same as those in Example 1.
[0101] Comparative Example 5 Comparative Example 5 is basically the same as Example 1, except that a polytetrafluoroethylene limiting frame is not set, and other conditions are the same as in Example 1.
[0102] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, except that the thickness of the copper capillary layer is 10 μm, the height of the flexible support rib is adjusted to 50 μm, the height of the three-dimensional phase change cavity is kept at 60 μm, and other conditions are the same as in Example 1.
[0103] Comparative Example 7 Comparative Example 7 is basically the same as Example 1, except that the spacing between the flexible support ribs is 2.50 mm, and the other conditions are the same as those in Example 1.
[0104] Comparative Example 8 Comparative Example 8 is basically the same as Example 1, except that the sintering temperature of the copper capillary layer and the flexible support rib is 500°C and the sintering time is 10 min. Other conditions are the same as in Example 1.
[0105] Comparative Example 9 Comparative Example 9 is essentially the same as Example 1, except that the gallium indium tin liquid alloy heat conduction unit is removed, while the microgroove confinement region, the nickel metal interface layer, and the polytetrafluoroethylene (PTFE) limiting frame are retained. Other conditions are the same as in Example 1. This comparative example is used to examine the interaction between the microgroove confinement region, the nickel metal interface layer, and the gallium indium tin liquid alloy heat conduction unit.
[0106] Comparative Example 10 Comparative Example 10 is essentially the same as Example 1, except that the nickel interface layer only continuously covers 50% of the bottom area of the microgroove confinement region. The bottom and wall areas not covered by the nickel interface layer are in direct contact with the gallium indium tin liquid alloy heat conduction unit. Other conditions are the same as in Example 1. This comparative example is used to examine the cooperation between the nickel interface layer coverage state and the gallium indium tin liquid alloy heat conduction unit.
[0107] Comparative Example 11 Comparative Example 11 is essentially the same as Example 1, except that the microgroove confinement region is removed. A flat thermally conductive surface is formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity. A 0.2 μm thick nickel interface layer is deposited on the flat thermally conductive surface, continuously covering 100% of the designated planar thermally conductive area. A gallium indium tin liquid alloy thermal conduction unit is spread with an equivalent exposed thickness of 3 μm on the inner side of the flat thermally conductive surface. The polytetrafluoroethylene confinement frame is still set around the perimeter of this area. Other conditions are the same as in Example 1. This comparative example is used to investigate the influence of the microgroove confinement structure on the spatial distribution of the liquid alloy and the interface thermal conductivity.
[0108] Characterization and performance testing The test subjects were Examples 1-4 and all comparative examples, with the aim of evaluating the interfacial thermal resistance between the flexible fully bonded surface and the heating element. The samples were clamped between a flat copper heat source block and a water-cooled block. The interfacial thermal resistances in Table 1 were measured under uniform conditions: installation pressure 0.080 MPa, heat input 40 W, effective heat source contact area 10 mm × 10 mm, and cold end water temperature 25℃ ± 1℃. A steady state was defined as a temperature fluctuation not exceeding 0.2℃ within 5 consecutive minutes. The temperature difference between the hot and cold end reference surfaces was recorded using a steady-state thermal resistance fixture calibrated with a blank fixture. The interfacial thermal resistance was calculated as Rinterface = (Th - Tc) / Q - R0, where Th is the hot end reference surface temperature, Tc is the cold end reference surface temperature, Q is the input heat power, and R0 is the calibrated thermal resistance of the blank fixture. The test was repeated n = 3 times, and the average and standard deviation of the thermal resistance were recorded in K / W. A lower value indicates a smaller interfacial thermal resistance.
[0109] The test subjects were Examples 1-4 and all comparative examples, with the aim of evaluating the in-plane temperature uniformity of the vapor chamber. Heating ceramic sheets were attached to the corresponding positions within the microgroove confinement area. The heat input was 40W, the ambient temperature was 25℃±2℃, and the relative humidity was 50%±5%. A high-emissivity black marker layer with an emissivity of 0.95 was affixed to the temperature measurement area of the surface under test. The highest and lowest temperatures after stabilization for 10 minutes were recorded using a blackbody-calibrated infrared thermal imager. The average and standard deviation of the in-plane temperature difference were obtained, in °C; the lower the value, the better the in-plane temperature uniformity.
[0110] The test subjects were Examples 1-4 and a comparative example involving changes to the copper capillary support structure. The purpose was to evaluate the maximum heat transfer capacity and capillary reflux stability of the phase change cavity. The samples were placed horizontally, with a cold-end water temperature of 25℃±1℃. The heat input started at 10W and increased in 5W increments, with each increment held for 5 minutes. The temperatures of the evaporation zone, condensation zone, and stable operating heat load were recorded. When the average temperature increase in the evaporation zone between two adjacent heat load levels exceeded 10℃, and the subsequent level could not reach a stable state with temperature fluctuations not exceeding 0.5℃ within 5 minutes, the previous heat load was defined as the limiting heat load. The experiment yielded the average value and standard deviation of the limiting heat load, in W. Higher values indicate higher stable phase change heat transfer capacity.
[0111] The test subjects were Examples 1-4 and comparative examples involving changes to the liquid alloy confinement structure. The purpose was to evaluate the confinement stability of the gallium indium tin (CITi) liquid alloy heat conduction unit under installation pressure and thermal cycling. The samples were pressed together under 0.080 MPa pressure and subjected to 100 thermal cycles from 20°C to 80°C, with both heating and cooling rates of 5°C / min. The samples were held at 20°C and 80°C for 10 min each. After cycling, the overflowing liquid alloy outside the PTFE confinement frame was collected, and the coverage area was statistically analyzed using microscopic images.
[0112] The liquid alloy retention rate η is calculated as η = mr / m0 × 100%, where m0 is the initial mass of the liquid alloy located in the microgroove confinement area and the PTFE confinement frame before thermal cycling, and mr is the mass of the liquid alloy retained in the microgroove confinement area and the PTFE confinement frame after thermal cycling, after deducting the liquid alloy overflowing outside the PTFE confinement frame. Samples without a gallium indium tin liquid alloy thermal conduction unit are not included in the liquid alloy retention rate calculation.
[0113] The test subjects were Examples 1-4, Comparative Examples 1, 2, 10, and 11, with the aim of evaluating the microgroove confinement region, the nickel interface layer, and the liquid alloy filling state. Cross-sectional samples were prepared, and the microgroove dimensions, nickel interface layer thickness, nickel interface layer coverage, and area coverage were measured using scanning electron microscopy, energy dispersive spectroscopy (EDS), and a 3D profilometer. At least 30 locations were recorded for each sample.
[0114] For samples with microgroove confinement areas, the coverage rate of the nickel interface layer is the ratio of the projected area of the microgroove bottom continuously covered by nickel to the total projected area of the microgroove bottom; for samples with flat heat-conducting surfaces, the coverage rate of the nickel interface layer is the ratio of the area of the specified heat-conducting region continuously covered by nickel to the total area of the specified heat-conducting region.
[0115] The test subjects were Examples 1-4 and all comparative examples, with the aim of evaluating the sealing reliability of the enclosed shell and the three-dimensional phase change cavity. A helium mass spectrometer leak detector was used to detect the leakage rate of the samples. Before testing, the samples were left to stand at 25℃±2℃ for 24 hours, and after testing, they were kept at 60℃ for 24 hours and the leak detection was repeated. Helium was loaded using the helium hood method during testing, and the background signal, peak signal, and leak detector calibration value were recorded. The leakage rate was taken as the average of three tests, expressed in Pa·m. 3 / s.
[0116] Table 1 Performance of Examples and Comparative Examples
[0117]
[0118] In Comparative Example 11, the coverage of the nickel interface layer was statistically analyzed based on the specified planar thermally conductive area; for the other samples with microgroove confinement areas, the projected area of the bottom of the microgroove was statistically analyzed.
[0119] like Figure 1As shown, the liquid alloy retention rates of Examples 1, 5, and 11 during 0-100 thermal cycles were tested. The test results show that after 100 thermal cycles, the liquid alloy retention rate of Example 1 was 99.0 ± 0.3 wt%; the liquid alloy retention rates of Comparative Examples 5 and 11 under the same thermal cycling conditions were 88.0 ± 1.5 wt% and 86.5 ± 1.8 wt%, respectively. In Example 1, the microgroove confinement region, the nickel interface layer, and the PTFE confinement frame collectively restrict the edge migration of the liquid alloy.
[0120] like Figure 2 As shown, the limiting heat load and in-plane temperature difference of Example 1, Comparative Example 7, and Comparative Example 8 are compared. The limiting heat load of Example 1 is 58±2W, and the in-plane temperature difference is 4.8±0.3℃; the limiting heat loads of Comparative Example 7 and Comparative Example 8 are 45±2W and 47±2W, respectively, and the in-plane temperature differences are 5.7±0.3℃ and 5.9±0.4℃, respectively. Under the test conditions, the copper capillary layer, the spacing of the flexible support ribs, and the sintering state affect the maintenance of the vapor channel and the capillary reflux state.
[0121] like Figure 3 As shown, the changes in interfacial thermal resistance of Examples 1, 8, and 11 before and after 0-100 thermal cycles were tested. The interfacial thermal resistance of Example 1 increased from an initial 0.185 K / W to 0.193 K / W; the interfacial thermal resistances of Comparative Examples 8 and 11 were 0.248 K / W and 0.258 K / W, respectively, after 100 thermal cycles. These results indicate that under the stated thermal cycling conditions, the change in interfacial thermal resistance of Example 1 is relatively small.
[0122] like Figure 4 As shown, based on the baseline structure of Example 1, with other structural parameters and test conditions remaining consistent, only the tank filling rate was adjusted from 20 vol% to 100 vol%, and the changes in interfacial thermal resistance and liquid alloy retention rate were tested. When the tank filling rate increased from 20 vol% to 60 vol%, the interfacial thermal resistance decreased from 0.241 K / W to 0.150 K / W; when the filling rate increased to 100 vol%, the interfacial thermal resistance was 0.205 K / W, and the liquid alloy retention rate was 92.0 wt%. Under these test conditions, a tank filling rate of 30-90 vol% can balance the formation of thermal conduction pathways in the liquid alloy and confinement stability.
[0123] like Figure 5 As shown, Figure 5 a is a macroscopic optical photograph of the final product of Example 1. Figure 5b is a macroscopic optical photograph of the final product of Comparative Example 11. The sample obtained in Example 1 was a sheet-like thin 3DVC vapor chamber, with a microgroove confinement region approximately 10 μm deep, 20 μm wide, and 50 μm apart between the centerlines of adjacent microgrooves on its flexible, fully bonded surface. The grooves were filled with a gallium indium tin liquid alloy with an equivalent exposed thickness of approximately 3 μm. The overall dimensions and material composition of Comparative Example 11 were basically the same as in Example 1, but the microgroove confinement region was eliminated, and the gallium indium tin liquid alloy was spread only on a flat, heat-conducting surface. In Example 1, the liquid alloy was distributed within a regular microgroove region, while in Comparative Example 11, the liquid alloy was spread out on a flat, heat-conducting surface.
[0124] like Figure 6 As shown, the microstructure of the outer heat-conducting area of Example 1 and Comparative Example 11 was further observed by SEM. Figure 6 a and Figure 6 b represents the medium-magnification surface SEM morphology of both. Figure 6 c and Figure 6 d represents the cross-sectional SEM morphology of both. In the cross-sectional SEM of Example 1, a microgroove structure, a nickel interface layer located at least partially on the bottom and walls of the groove, a gallium indium tin liquid alloy located within the microgroove, and a local Cu / Ni / GaInSn composite interface can be observed; Comparative Example 11 mainly presents a planar Cu / Ni / GaInSn contact interface.
[0125] Based on the performance data of each embodiment and comparative example in Table 1, it can be seen that Embodiments 1-4 have different parameter matching relationships in terms of interfacial thermal resistance, in-plane temperature difference, ultimate thermal load, liquid alloy retention rate, and sealing reliability. Among them, Embodiment 1 is suitable for structures with smaller outer thickness and lower liquid alloy exposure; Embodiment 2 has lower interfacial thermal resistance and higher ultimate thermal load; Embodiments 3 and 4 balance interfacial thermal conductivity and liquid alloy confinement under medium thickness conditions.
[0126] In contrast, when the nickel interface layer, microgroove depth, groove filling rate, PTFE confinement frame, copper capillary layer thickness, flexible support rib spacing, sintering conditions, nickel interface layer coverage, or microgroove confinement structure are changed or removed in the comparative examples, at least one of the following changes occurs: interface thermal resistance, in-plane temperature difference, ultimate thermal load, or liquid alloy retention rate. Comparative Example 9 did not include a gallium indium tin liquid alloy heat conduction unit, therefore the liquid alloy retention rate was not calculated.
[0127] In conclusion, Figures 1 to 6 The test results in Table 1 show that the capillary support structure composed of the internal copper capillary layer and flexible support ribs, and the flexible fully bonded structure composed of the external microgroove confinement area, the nickel metal interface layer, the gallium indium tin liquid alloy heat conduction unit and the polytetrafluoroethylene limiting frame, can be used to form a thin 3DVC heat spreader that combines phase change heat transfer, interface heat conduction and liquid alloy confinement functions.
[0128] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. An energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure, characterized in that, include: A closed shell, comprising a first copper sheet and a second copper sheet, wherein the first copper sheet and the second copper sheet are sealed at the periphery, and a three-dimensional phase change cavity is formed inside the closed shell; A copper capillary support structure is disposed in the three-dimensional phase change cavity. The copper capillary support structure includes a copper capillary layer and a plurality of flexible support ribs connected to the copper capillary layer. The plurality of flexible support ribs extend from the copper capillary layer toward another copper sheet and form a support contact with the other copper sheet after being sealed by the closed shell. A steam channel is formed between the plurality of flexible support ribs. Deionized water, which is encapsulated in the three-dimensional phase change cavity and serves as a phase change heat transfer medium; A flexible fully-fitted surface is located on the side of the first copper sheet facing away from the three-dimensional phase change cavity. The flexible fully-fitted surface includes a microgroove confinement area corresponding to the heating element of the electronic device. A nickel interface layer, the nickel interface layer covering at least a portion of the bottom and wall of the microgroove confinement region; A liquid alloy heat conduction unit, wherein the liquid alloy heat conduction unit is at least partially confined and filled within the microgroove confinement area and is in contact with the metallic nickel interface layer; And a polytetrafluoroethylene (PTFE) limiting frame, the PTFE limiting frame being disposed around the periphery of the microgroove confinement area; The microgroove confinement area is used to confine and accommodate the liquid alloy heat conduction unit, and the liquid alloy heat conduction unit forms an exposed heat conduction interface on one side of the flexible full-fit surface.
2. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1, characterized in that, Both the first copper sheet and the second copper sheet use copper as the main heat conductor. The copper capillary layer and the flexible support rib are both formed of copper. The nickel interface layer is formed of nickel. The liquid alloy heat conduction unit is a gallium indium tin liquid alloy heat conduction unit, which includes gallium, indium, and tin. The polytetrafluoroethylene limiting frame is formed of polytetrafluoroethylene. The maximum total thickness of the energy-saving 3DVC heat spreader is 0.25-1.20 mm, the microgroove depth of the microgroove confinement area is 10-120 μm, the microgroove width is 20-300 μm, the spacing between the center lines of adjacent microgrooves is 50-800 μm, and the microgroove depth is less than the single-piece thickness of the first copper sheet. Based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit, the content of gallium is 68.0-69.5 wt%, the content of indium is 20.5-22.5 wt%, and the content of tin is 9.0-11.0 wt%, and the combination of the contents of gallium, indium, and tin satisfies the condition that the total content of the three is 99.0-100.0 wt%. The gallium indium tin liquid alloy heat conduction unit occupies 30-90% of the total volume of the microgroove confinement area, and the equivalent exposed thickness of the gallium indium tin liquid alloy heat conduction unit on the flexible fully bonded surface side is 3-50μm.
3. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1 or 2, characterized in that, The gallium indium tin liquid alloy heat conduction unit is prepared through the following steps: A1. Weigh 68.0-69.5 wt% of metallic gallium, 20.5-22.5 wt% of metallic indium and 9.0-11.0 wt% of metallic tin based on the total mass of the metal components in the gallium-indium-tin liquid alloy heat conduction unit to be prepared; A2. The gallium metal, the indium metal, and the tin metal are melted and stirred to form a homogeneous molten metal phase; A3. Under a nitrogen or argon atmosphere, the oxide film on the surface of the homogeneous molten metal phase is removed using a ceramic scraper; A4. Cool the homogeneous molten metal phase after removing the oxide film to 20-30°C to obtain the gallium indium tin liquid alloy thermal conductivity unit; A5. The gallium indium tin liquid alloy thermal conductivity unit meets the following quality control parameters: the total content of the metallic gallium, the metallic indium and the metallic tin is 99.0-100.0 wt%, the oxygen content is 10-1000 ppm, and it remains liquid at 20-30℃ without solid phase precipitation.
4. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1 or 2, characterized in that, The microgroove confinement region and the nickel interface layer are formed through the following steps: B1. Provide the first copper sheet; B2. The microgroove confinement region is formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity by precision stamping, laser processing or chemical etching. The microgroove depth of the microgroove confinement region is 10-120μm, the microgroove width is 20-300μm, the spacing between the center lines of adjacent microgrooves is 50-800μm, and the microgroove depth is less than the thickness of a single piece of the first copper sheet. B3. Physical vapor deposition is performed on the microgroove confinement region using metallic nickel as the deposition source; B4. A nickel interface layer with a thickness of 0.2-5.0 μm is formed on at least a portion of the surface of the bottom and wall of the microgroove confinement region; B5. The size variation coefficient of the microgroove confinement region is 1-15%, and the nickel metal interface layer continuously covers 80-100% of the bottom area of the microgroove confinement region.
5. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1 or 2, characterized in that, The copper capillary support structure is formed through the following steps: C1. Copper is selected as the capillary material, wherein the capillary material is one or more of copper powder, copper mesh or copper fiber, wherein the particle size of the copper powder is 5-80 μm, the pore size of the copper mesh is 20-200 μm, and the diameter of the copper fiber is 5-50 μm; C2. The capillary material is laid on the side of the first copper sheet or the second copper sheet facing the three-dimensional phase change cavity to form the copper capillary layer with a thickness of 20-250 μm; C3. A plurality of flexible support ribs with a height of 40-300μm, a width of 30-500μm, and a spacing of 0.20-2.00mm are formed on the copper capillary layer, and the top of the flexible support ribs abuts against another copper sheet after the first copper sheet and the second copper sheet are sealed together. C4. Sinter the capillary material and the flexible support rib; C5. After sintering, the copper capillary support structure is obtained by cooling. C6. The porosity of the copper capillary support structure is 35-75 vol, and the ratio of the bonding area between the copper capillary layer and the first or second copper sheet on which it is located is 70-100%.
6. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1 or 2, characterized in that, The three-dimensional phase change cavity includes an evaporation zone, a condensation zone, and a vapor channel connecting the evaporation zone and the condensation zone. The evaporation zone and the micro-groove confinement zone correspond to each other in the thickness direction. The filling rate of the deionized water in the three-dimensional phase change cavity is 10-40 vol.
7. The energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure according to claim 1 or 2, characterized in that, The liquid alloy heat conduction unit has an area coverage of 60-98% within the microgroove confinement area, and the mass of the free liquid alloy located within the polytetrafluoroethylene confinement frame and outside the microgroove confinement area accounts for 0-5 wt% of the total mass of the liquid alloy heat conduction unit.
8. A method for preparing an energy-saving 3DVC heat spreader with a flexible, fully-fitted capillary support structure as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Provide a first copper sheet and a second copper sheet, both of which use copper as the heat conduction substrate; S2. A microgroove confinement region is formed on the side of the first copper sheet facing away from the three-dimensional phase change cavity to be formed, and a nickel interface layer made of metallic nickel is formed on at least a portion of the bottom and wall of the microgroove confinement region. S3. A copper capillary support structure made of copper is formed on the side of the first copper sheet or the second copper sheet facing the three-dimensional phase change cavity to be formed; S4. The first copper sheet and the second copper sheet are joined and sealed to form a shell with a three-dimensional phase change cavity and a vacuum injection port connected to the three-dimensional phase change cavity; S5. After evacuating the three-dimensional phase change cavity through the vacuum injection port, deionized water that has undergone degassing treatment is injected and the cavity is sealed. S6. Using a pre-prepared liquid alloy heat conduction unit as raw material, and filling it into the microgroove confinement area; S7. A polytetrafluoroethylene (PTFE) limiting frame is provided around the periphery of the microgroove confinement area to obtain the energy-saving 3DVC heat spreader with a flexible, fully-fitting capillary support structure.
9. The preparation method according to claim 8, characterized in that, In step S2, the microgroove confinement area is formed by one of laser processing, precision stamping or chemical etching. The microgroove depth of the formed microgroove confinement area is 10-120μm, the microgroove width is 20-300μm, the spacing between the center lines of adjacent microgrooves is 50-800μm, and the microgroove depth is less than the single-piece thickness of the first copper sheet. In step S3, the copper capillary support structure is formed by copper powder sintering, copper mesh pressing and sintering, or copper fiber sintering. In step S4, the sealing method is one of laser welding, diffusion welding or brazing, and the height of the three-dimensional phase change cavity formed after sealing is 40-500μm. In step S5, the absolute pressure of the three-dimensional phase change cavity after vacuuming is 0.0000001-0.0005 MPa. The deionized water is degassed under vacuum at 50-80℃ and 0.005-0.020 MPa for 10-30 minutes before injection. The filling rate of the deionized water is 10-40 vol%. The total thickness of the sealed shell after sealing is 0.25-1.20 mm.
10. The preparation method according to claim 8, characterized in that, In step S6, after filling, the excess free liquid alloy located outside the microgroove confinement area is removed by scraping, so that the equivalent exposed thickness of the liquid alloy heat conduction unit on the side of the first copper sheet where the microgroove confinement area is formed is 3-50μm. After step S6 and before step S7, the microgroove confinement area is rolled and shaped with a rolling pressure of 0.020-0.200 MPa and a rolling number of 1-5 times, so that the liquid alloy heat conduction unit is confined within the microgroove confinement area. In step S7, the polytetrafluoroethylene limiting frame is continuously arranged around the microgroove confinement area; In the energy-saving 3DVC heat spreader with flexible fully bonded capillary support structure, the porosity of the copper capillary support structure is 35-75 vol%, the filling rate of the groove of the liquid alloy heat conduction unit is 30-90 vol%, and the polytetrafluoroethylene limiting frame is 5-50 μm higher than the exposed surface of the liquid alloy heat conduction unit on the side of the first copper sheet where the microgroove confinement area is formed.
Citation Information
Patent Citations
Ultra-thin even-temperature plate device and manufacturing method thereof
CN105352352A
Vapor chamber with sintered grooved wick
US6880626B2